What is a book?: the study of early printed books - Dane, Joseph A. (Univ. of Notre Dame Press, 2012)
"Joseph A. Dane's What Is a Book? is an introduction to the study of books produced during the period of the hand press, dating from around 1450 through 1800. Using his own bibliographic interests as a guide, Dane selects illustrative examples primarily from fifteenth-century books, books of particular interest to students of English literature, and books central to the development of Anglo-American bibliography. Part I of What Is a Book? covers the basic procedures of printing and the parts of the physical book--size, paper, type, illustration; Part II treats the history of book-copies--from cataloging conventions and provenance to electronic media and their implications for the study of books. Dane begins with the central distinction between a "book-copy"--the particular, individual, physical book--and a "book"--the abstract category that organizes these copies into editions, whereby each copy is interchangeable with any other. Among other issues, Dane addresses such basic questions as: How do students, bibliographers, and collectors discuss these things? And when is it legitimate to generalize on the basis of particular examples? Dane considers each issue in terms of a practical example or question a reader might confront: How do you identify books on the basis of typography? What is the status of paper evidence? How are the various elements on the page defined? What are the implications of the images available in an online database? And, significantly, how does a scholar's personal experience with books challenge or conform to the standard language of book history and bibliography? Dane's accessible and lively tour of the field is a useful guide for all students of book history, from the beginner to the specialist. "Written with wit and acuity, Joseph A. Dane's What Is a Book? extends his project of teaching aspects of book history to the specialist and nonspecialist reader alike. Both will be stimulated and provoked by what Dane writes, and will also enjoy his arguments and admire the breadth and depth of his knowledge." --Henry Woudhuysen, University College London"-